Meningkatkan Rasa Percaya Diri Anak Usia Dini melalui Metode Bercerita (Studi Kasus: Di RA Al-Falah Karang Sentul Kecamatan Gondang Wetan Kabupaten Pasuruan) - M. Mujib Utsmani; Maulidiatul Hasanah (LP3M STITNU AL HIKMAH MOJOKERTO, 2021)
Teachers or educators in Kindergarten must be able to choose and determine the appropriate method will be used to foster self-confidence in early childhood and adapted to the level of development of kindergarten children as well. Application of the method that has not been maximally done by educators and children are less active at the time learning takes place, making children's self-confidence still classified as low. Various efforts have been made by teachers in RA Al-Falah Kindergarten are like giving opportunities to students children while serving as ceremonial officers, leading prayers before starting activities and prepare friends at the time of marching. The formulation of the problem that the researcher proposes is: Why is the application of The storytelling method has not been able to foster self-confidence in early childhood in Indonesia RA Al-Falah Karang Sentul Gondang Wetan Pasuruan ?. Research purposes namely to find out the application of the storytelling method can grow self-confidence in early childhood in Al-Falah Kindergarten. Research that used is descriptive qualitative research. The research subjects were 19 children students, while the object of research is the application of the storytelling method to develop self-confidence in young children. Data collection techniques that used are observation, interviews, documentation. Based on the results of the author's research, lack of self-confidence in children by applying the storytelling method because in storytelling activities there are the steps that must be considered by the teacher such as the selection of storytelling methods, classroom management for storytelling, management of seating and storytelling rooms, and the strategy of storytelling there are only 3 steps that have been implemented.